Beyond binary: K‐12 student use of gender‐inclusive language in a scientific context. (30th March 2023) - Miller, Jocelyn; Olson, Missie; Bryant, Connor; Hite, Rebecca; Childers, Gina
Abstract: Studies suggest that the lack of diversity in the science workforce may be partially attributed to implicit bias. Collectively, implicit biases are ingrained among youth from their upbringing, culture, and media, which are subsequently reflected in their language choices. Reform efforts made in post‐secondary science education have targeted implicit bias by challenging the use of gendered language (he, she) and modeling gender inclusive language. However, the impact of such reforms are unexplored among K‐12 aged learners. Utilizing the theoretical lens of implicit cognition, student‐produced text within 288 primary ( n = 47) and secondary ( n = 241) Draw a Scientist Tests (DASTs) were analyzed using critical discourse analysis to explore how gender‐exclusive language (GEL) and gender‐inclusive language (GIL) was used by students when describing scientists. Findings suggest that middle school boys were most likely to use GIL, whereas high school girls were the least likely to use GIL. However, when specifying gender, elementary boys were most likely to use male‐exclusive language, and high school girls were the most likely to use female‐exclusive language. Further analyses suggest that students' implicit perceptions of scientists (character traits, academic behaviors, the field of study) were influenced by their gender, grade level, and the scientist's perceived gender or gender neutrality.